Seroprevalence of Helicobacter pylori in Hispanics living in Puerto Rico: A population‐based study. Issue 1 (6th December 2017) - González‐Pons, María; Soto‐Salgado, Marievelisse; Sevilla, Javier; Márquez‐Lespier, Juan M.; Morgan, Douglas; Pérez, Cynthia M.; Cruz‐Correa, Marcia
Abstract: Background: Helicobacter pylori is an important etiologic factor for peptic ulcers and gastric cancer, one of the top ten leading causes of cancer death in Puerto Rico. However, the prevalence of H. pylori infections in this population was previously unknown. The aim of this study was to examine the seroprevalence of H. pylori and its associated risk factors in Puerto Rico. Materials and Methods: A cross‐sectional study was designed using an existing population‐based biorepository. Seropositivity was determined using the Premier ™ H. pylori immunoassay. Helicobacter pylori seroprevalence was estimated with 95% confidence using marginal standardization following logistic regression. To assess the risk factors associated with H. pylori seropositivity, a multivariable log‐binomial model was fitted to estimate the prevalence ratio (PR) and its 95% confidence interval (95% CI). Results: A total of 528 population‐based serum samples were analyzed. The mean age of the study population was 41 ± 12 years, of whom 55.3% were females. The overall seroprevalence of H. pylori was 33.0% (95% CI = 28.3%‐38.1%). Increasing age and having <12 years of education were significantly ( P < .05) associated with H. pylori seropositivity in the multivariable model; however, residing in counties with low population density reached marginal significance ( P = .085). Conclusions: We report that H. pylori infection is common among Hispanics living in Puerto Rico. The H. pylori seroprevalence observed in Puerto Rico is similar to the seroprevalence reported in the overall population of the United States. The association between H. pylori seroprevalence and the risk factors analyzed offers insight into the epidemiology of gastric cancer in Puerto Rico and warrants further investigation.